Biomechanical comparison between pins and polymethylmethacrylate and the SOP locking plate system to stabilize canine lumbosacral fracture‐luxation in flexion and extension. Issue 6 (24th May 2017) - Nel, Johannes J.; Kat, Cor‐Jacques; Coetzee, Gert L.; van Staden, Paul J.
Abstract: Objective: To determine the stability of a simulated complete L7‐S1 fracture‐luxation immobilized with SOP locking plate system, compared to pins and polymethylmethacrylate (PMMA). Study design: In vitro biomechanical study. Animals: Cadaver specimens of 18 skeletally mature large‐breed dogs. Materials and Methods: Specimens were randomly stabilized with one of the two fixation techniques. Lumbosacral spine specimens (L5‐S3) were subjected to a bending moment applied to the caudal and cranial ends of the specimen. The biomechanical parameters (ie, range of motion [ROM], neutral zone [NZ], and elastic zone stiffness [EZS]) were compared between fixation techniques. Results: No difference was found between the means of the NZ in flexion ( P = .3458), extension ( P = .1255), and total value ( P = .3458) of L7‐S1 stabilized with the two fixation techniques. Mean ROM in flexion ( P = .2386), extension ( P = .1255), and mean of EZS in extension ( P = .4094) did not differ between fixations. The only significant differences were in the means of total ROM and means of the EZS in flexion, with the means being smaller with SOP fixation. Conclusion: The stability of the two fixation techniques in flexion and in extension was similar for the L7‐S1 and adjacent L5‐L6 junctions, while the mean of ROM of L6‐L7 in flexion was smaller with SOP fixation. Clinical Relevance: Stability of the resulting construct should be considered when selecting an implant. Our results provide evidence that fixation via pin‐PMMA or SOP provide similar stability for L7‐S1 fracture‐luxation. In this context, other factors become more important in selecting the fixation method.